2017
DOI: 10.1111/eva.12549
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term on‐farm participatory maize breeding by stratified mass selection retains molecular diversity while improving agronomic performance

Abstract: Modern maize breeding programs gave rise to genetically uniform varieties that can affect maize's capacity to cope with increasing climate unpredictability. Maize populations, genetically more heterogeneous, can evolve and better adapt to a broader range of edaphic–climatic conditions. These populations usually suffer from low yields; it is therefore desirable to improve their agronomic performance while maintaining their valuable diversity levels. With this objective, a long‐term participatory breeding/on‐far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Our genetic results were similar to those found by [23] (comparing two open-pollinated maize populations undergone to stratified mass selection for 19 and 25 years) and to those found by [20] (comparing two maize synthetic varieties after two cycles RRS) who found that the genetic differentiation among versions of the same population was very low.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our genetic results were similar to those found by [23] (comparing two open-pollinated maize populations undergone to stratified mass selection for 19 and 25 years) and to those found by [20] (comparing two maize synthetic varieties after two cycles RRS) who found that the genetic differentiation among versions of the same population was very low.…”
Section: Discussionsupporting
confidence: 90%
“…Of course, a longer breeding period or a different selection method than implemented in this study could have allowed a greater differentiation among populations. For example, as suggested by results of [23], in which the final versions of two maize populations showed low differentiation from the original populations, mass selection resulted less selective than a RRS implemented for a similar period [18]. In addition, in both maize mass and RSS, a long breeding program increased the genetic differentiation among original and final breeding populations [18,49], probably as a consequence of allele fixation [18,50].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, genetic changes in maize composite populations under Reciprocal Recurrent Selection (RRS) were analyzed by using Restriction Fragment Length Polymorphism (RFLP) [17,18], Simple Sequence Repeats (SSR) [19][20][21] and Single Nucleotide Polymorphism (SNP) [22]. SSR were also used in order to evaluate the genetic changes in different maize populations obtained after about 20 years of stratified mass selection on two historical Portuguese populations [23]. Considering autogamous species, the genetic evolution over time and space of wheat CCP was assessed by RFLP [24,25] and by SSR [26] and that of a barley CCP by using SSR [13].…”
mentioning
confidence: 99%